HADITS DAN AKTIFITAS IMANIYAH PADA TAHAPAN PERKEMBANGAN INDIVIDU - M. Noor Fuady (Postgraduate State Islamic Institute (IAIN) Metro, 2022)
The role of parents in educating their children is pivotal (highly important) and more specifically in cultivating the faith values. This article is intended to examine that individual faith values development and its responsibility on each stage by analyzing the hadiths of the Prophet Muhammad, Peace Be Upon Him (PBUH) which explain about the issue, and then describe and exemplify those faith values activities that could be done by parents on each individual development stage. Maudhu'i method is used to completely examine this issue.